Mitigating Child Stunting: Community-Based Strategies in Maibo Village, Sorong Regency, Indonesia - Andriany, Alia; Ahmar, Hamdiah; Sianturi, Sintong Halomoan (Journal of Current Health Sciences, 2025)
Stunting significantly impairs cognitive development, potentially leading to long-term intellectual disabilities, compromised learning abilities, and an elevated risk of chronic illnesses. This study investigates the prevalence and determinants of stunting among toddlers in Maibo Village, Aimas District, Sorong Regency, employing a descriptive quantitative approach. Data were sourced from the 2024 Sorong District Health Office report covering 19 public health centers, focusing specifically on Malawili Health Center. Spatial-temporal analyses revealed high stunting prevalence rates in Seget (44.1%), Makbon (37.4%), and Maudus (36.6%) health centers, whereas Maibo Village had a lower prevalence rate of 17.22%. A concerning increase in stunting cases was observed at Malawili Health Center from 92 in 2021 to 261 cases in 2024. Key local determinants identified include limited nutritional access, inadequate sanitation, and socioeconomic challenges. The findings highlight the necessity of targeted nutritional education, particularly regarding balanced diets, exclusive breastfeeding, and appropriate complementary feeding, to be delivered through community-based programs and healthcare services. These interventions, supported by strengthened cross-sectoral collaboration between local governments, private entities, and communities, are critical for mitigating stunting prevalence. Future qualitative research is recommended to deepen the understanding of community-specific nutritional practices and enhance the effectiveness of intervention strategies.